Pengaruh Strategi Mindfull Learning terhadap Kemampuan Metakognisi Siswa Kelas IV MI Islamiyah Muhammadiyah Walikukun - Yuliana Ayu Febriarianti; Sumarno; Ahsan Hakim (Jurnal Pendidikan Indonesia, 2026)
Abstract. This study aims to describe the implementation of the mindful learning strategy, map metacognitive profiles, and analyze the influence of the strategy on the metacognitive skills of fourth-grade students at MI Islamiyah Muhammadiyah Walikukun. The primary background is the low reflective awareness and the dominance of conventional teaching methods. This research employed a quantitative approach with a quasi-experimental design, specifically the Non-equivalent Control Group Design. The sample consisted of 66 students divided into experimental and control groups. Data were collected through metacognitive tests (planning, monitoring, and evaluation) and observation sheets, then analyzed using the Independent Sample T-Test. The results showed that the mindful learning strategy was optimally implemented (100%) by the second meeting. There was a significant increase in the experimental group’s average metacognitive score from 68.90 to 84.42, with students in the high category jumping to 48%. Statistical testing yielded a significance value of 0.000 (< 0.05), leading to the rejection of the null hypothesis. It is concluded that the mindful learning strategy significantly influences the improvement of students’ metacognitive skills through mindfulness practices and deep reflection, which help students manage their thinking processes independently.